Membrane vesicles derived from Bordetella bronchiseptica: Active constituent of a new vaccine against infections caused by this pathogen - Bottero, Daniela (2018)
Bordetella bronchiseptica, a Gram-negative bacterium, causes chronic respiratory tract infections in a wide variety of mammalian hosts, including humans (albeit rarely). We recently designed Bordetella pertussis and Bordetella parapertussis experimental vaccines based on outer membrane vesicles (OMVs) derived from each pathogen, and we obtained protection against the respective infections in mice. Here, we demonstrated that OMVs derived from virulent-phase B. bronchiseptica (OMVBbvir+) protected mice against sublethal infections with different B. bronchiseptica strains, two isolated from farm animals and one isolated from a human patient. In all infections, we observed that the B. bronchiseptica loads were significantly reduced in the lungs of vaccinated animals; the lung-recovered CFU were decreased by ≥4 log units, compared with those detected in the lungs of nonimmunized animals (P < 0.001). In the OMVBbvir+-immunized mice, we detected IgG antibody titers against B. bronchiseptica whole-cell lysates, along with an immune serum having bacterial killing activity that both recognized B. bronchiseptica lipopolysaccharides and polypeptides such as GroEL and outer membrane protein C (OMPc) and demonstrated an essential protective capacity against B. bronchiseptica infection, as detected by passive in vivo transfer experiments. Stimulation of cultured splenocytes from immunized mice with OMVBbvir+ resulted in interleukin 5 (IL-5), gamma interferon (IFN-γ), and IL-17 production, indicating that the vesicles induced mixed Th2, Th1, and Th17 T-cell immune responses. We detected, by adoptive transfer assays, that spleen cells from OMVBbvir+-immunized mice also contributed to the observed protection against B. bronchiseptica infection. OMVs from avirulent-phase B. bronchiseptica and the resulting induced immune sera were also able to protect mice against B. bronchiseptica infection.